HERITABILITY ESTIMATES OF SOME LINEAR TYPE TRAITS IN NILI RAVI BUFFALOES - R. H. Mirza; K. Javed; M. Abdullah; T. N. Pasha; M. Akhtar (Journal of Animal and Plant Sciences, 2015)
Most of the body conformation traits are heritable to varying levels and have been reported in almost all of the important dairy cattle breeds. Traits showing medium to high heritability estimates can be improved through selection and breeding depending upon the selection intensity and heritability of a particular trait. The present study was planned for the characterization of linear type traits in Nili Ravi buffaloes of Pakistan. One of the main objectives of the study was the genetic evaluation of Nili Ravi buffaloes for body conformation and linear type traits. A total of 1180 records on 437 Nili Ravi milking buffaloes were generated over a scoring period of two years. Pedigree records of buffaloes were traced back up to 5 available generations and these buffaloes were the progeny of 88 sires and 303 dams. Number of base animals were 119 with no pedigree records. Univariate heritability estimates of linear type traits using ASREML computer program (Gilmour, 2009) showed that most of the estimates were low to medium in range. Heritability estimates for stature, chest width, body depth, angularity, rump angle and rump width were found as 0.36±0.092, 0.10±0.081, 0.32±0.081, 0.06±0.071, 0.15±0.071, and 0.38±0.092, respectively. Heritability estimates for most of the linear type traits were found in agreement with the reports available in the literature for different dairy cattle breeds. The results might be considered for inclusion of some of the linear type traits in selection programs. However, consideration of correlation of any trait with milk yield is a prerequisite because in case of positive correlation with milk yield, improvement in both milk yield and a linear trait will be simultaneous but in case of negative correlation the case may be reverse. Among the body conformation traits, stature, body depth, rump angle and rump width are relatively more important and should be given consideration. Further studies and research with larger data set is needed to explore linear type traits and to validate the findings of the current study.
Keywords: Heritability; linear type traits; Nili Ravi Buffalo; Pakistan